Fractal theory applied to image processing - Nguyễn Văn Phúc; Lê Tiến Thường (Journal of Technical Education Science, 2012)
The Euclidean geometry defines the dimension of objects as a positive integer. This permits to describe the artificial objects such as a square, a circle, a triangle, a pyramid…Using this geometry, we cannot fully describe the more complex natural objects such as clouds, mountains, glasses, trees, coastlines…Fractal stands for Fractional Dimension. The Fractal geometry defines the dimension of objects as a fractal number. This geometry is an expansion of the classical Euclidean geometry. It can describe the natural objects fully and particularly. Iterative function systems are used for these descriptions. This paper uses the theory of Fractal geometry to create the background images on computers, on mobile phones and some Fractal images are deployed on the LM3S2965 32 bits ARM - Cortex Kit